Production and recovery of rhamnolipids using sugar cane molasses as carbon source - Santos, Everaldo Silvino dos (2021)
Biosurfactants were synthesized by Pseudomonas aeruginosa (P.A.), using sugar cane molasses as carbon source. Assays were conducted in a shaker with agitation speed of 200 rpm, temperature of 38 °C and aeration ratio (Vm/Vf) of 0.4 and 0.6. A concentration of 3.0% was used for the carbon and energy source (molasses) and of 0.3% for the nitrogen source (NaNO3). Samples were removed at regular times until 96 hours of cultivation. The reduction in surface tension was measured using the ring method; cell concentration was obtained by the dry mass and substrate consumption by the DNS method. The metabolite produced was extracted and quantified by the thioglycolic method. The results showed a maximum surface tension reduction of 46.57% after 60 h, 3.63 g/L of biomass after 8 h (μXmáx =0.15 h-1), 79.60% of substrate consumption (μs= 0.67 h-1) and 4.47 g/L of rhamnolipid (μp=0.029 h-1)